Perancangan E-Magazine sebagai Referensi Program untuk Perpustakaan Sekolah Menengah Atas (Design and Development di Perpustakaan Sekolah Negeri se-Kota Bandung) - Achmad Riyadi Alberto; Rangga Agung Primayadi; Tiara Sugih Hartati (Perpustakaan Nasional, 2021)
The Covid-19 pandemic has made school libraries unable to provide their services, plus there is still a lack of school library programs to respond to the way of learning from offline to online. Even though libraries can use technology to continue to provide services for their users. The purpose of this research is to design library e-magazines at High School Libraries in Bandung city as a form of innovation for school library programs that can be run in the midst of the Covid-19 pandemic. This research can be used as an e-magazine blueprint that can be used at other school libraries. The research using a design and development model. The design of the e-magazine consists of three processes: 1) pre-production, which includes determining the theme, searching for articles, writing articles and correcting the text; 2) production, including magazine design, proofreading of design results, and trial printing; and 3) post-production, including printing and marketing. The results of the needs analysis show that suitable content in e-magazine are light reading types such as short stories, tips and tricks, various recommendations such as food, tourist attractions, movies, and books, as well as light like crossword puzzles. The response of librarians and students to the e-magazine is very good in terms of theme selection, material and language, and appearance. It is stated that the chosen theme is very relevant to the conditions and needs that occur. The responses obtained can then be used as an illustration and evaluation material for the next e-magazine design.